Approximation methods in the theory of operator inclusions - rahman mohammed, Hisham (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
In the present paper we use approximation methods for the study of operator inclusions of the form , where a is a closed linear surjective operator from a Banach space onto another one, and Î¦ is a multimap being a composition of a multimap with â€goodâ€ values and a continuous singlevalued map. As application we consider the solvability of an integro- diï¬€erential system which may be treated as a control object with an integral feedback. Key Words and Phrases: multivalued map, ï¬xed point, coincidence point, continuous selection, operator inclusion, closed linear operator, integro-differential system.